A rare case of esophageal diverticulum with classical presentation (Indian Journal of Case Reports, 2018)
Diverticula of the esophagus are rare, accounting for <1% of all barium gastrointestinal radiographs and <5% of all cases of dysphagia. Here, we report a case of an 80-year-old male presented with the chief complaint of dysphagia for 8 months. Contrast studies with barium swallow and computed tomography (CT) scan were performed to diagnose the etiology behind dysphagia, and it turned out to be a case of esophageal diverticulum which demonstrates outpouching from the wall of the esophagus in barium swallow and CT scan. These investigating modalities also aid in eliminating other causes of dysphagia.